2020
DOI: 10.1109/access.2020.3029458
|View full text |Cite
|
Sign up to set email alerts
|

A System Dynamics Model for Safety Supervision of Online Car-Hailing From an Evolutionary Game Theory Perspective

Abstract: Car-hailing safety supervision is of great significance to ease the pressure on urban public transportation and facilitate people to travel safely and conveniently. In this paper, a novel tripartite evolutionary game theory is proposed to describe the interaction mechanism of the government supervision department, online vehicle platform security monitoring department, and car sharing owner in the process of China's Internet ride-hailing operation. The replication dynamics equations are used to elaborate the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Apple eliminates some previously essential third-party applications in every new operating system released. Research has shown that a balance of competition and cooperation between platform enterprises and participants drives stable platform ecosystem development [30]. Therefore, if the government can correct this imbalance of competition and cooperation through an appropriate regulatory mechanism, stable development of the platform ecosystem can be promoted.…”
Section: A Platform Ecosystemmentioning
confidence: 99%
“…Apple eliminates some previously essential third-party applications in every new operating system released. Research has shown that a balance of competition and cooperation between platform enterprises and participants drives stable platform ecosystem development [30]. Therefore, if the government can correct this imbalance of competition and cooperation through an appropriate regulatory mechanism, stable development of the platform ecosystem can be promoted.…”
Section: A Platform Ecosystemmentioning
confidence: 99%
“…As a new mode of transportation and travel services that has emerged in China in recent years, network booking taxi provides passengers with greater travel convenience and personalized service supply. However, the studies by Cosenz [1] and Wang [2] further illustrate that companies are currently investing more in security, but are not clear about the direction of their focus. And because of the uncertainty of the direction of investment in safety operation resulting in safety investment, return is not a fully positive ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of modern mobile communication technology and big data has created a highly connected era in the current society [1]. As a new type of transportation service format OCH (online car-hailing) service mode is the core innovation and development performance of the integration of big data and transportation.…”
Section: Introductionmentioning
confidence: 99%